On Fuzzy BRK Topological Action. Issue 1 (January 2021) - Sivakumar, S.; Kousalya, S.
Abstract: In this paper, we consider fuzzy BRK topological group in a fuzzy action. We discuss some properties of a fuzzy BRK topological action and also some of their fuzzy relations on a group. Fuzzy BRK topological orbit of a fuzzy action also discuss.